SENOLYTICS – A DISCOVERY THAT COULD TRANSFORM THE COURSE OF AGING AND CHRONIC DISEASES - Kamil Kania; Marcel Bobiński; Zuzanna Wieczorek; Wiktoria Skowron; Justyna Bartol; Aleksandra Sosińska; Justyna Rajczyk; Monika Wiczuk–Wiczewska; Adam Szymczak; Tomasz Lepich (International Journal of Innovative Technologies in Social Science, 2026)
Senescent cells play a pivotal role in the progression of age-related diseases by promoting chronic inflammation and disrupting tissue function through the secretion of senescence-associated secretory phenotype (SASP) factors. Senolytics, a novel class of therapeutic agents, enable the selective elimination of these cells or the attenuation of their deleterious effects, offering a potential avenue to enhance healthspan. Preclinical studies and early clinical trials indicate that senolytics can improve cardiovascular function, metabolism, and physical performance, while demonstrating an acceptable safety profile. This review presents the mechanisms of action of senolytics, the current state of research, and their potential applications in metabolic, neurodegenerative, and cardiovascular diseases.